High-quality permanent draft genome sequence of Bradyrhizobium sp. strain WSM1743 - an effective microsymbiont of an Indigofera sp. growing in Australia. Issue 1 (December 2015) - Eshraghi, Leila; De Meyer, Sofie; Tian, Rui; Seshadri, Rekha; Ivanova, Natalia; Pati, Amrita; Markowitz, Victor; Woyke, Tanja; Kyrpides, Nikos; Tiwari, Ravi; Yates, Ron; Howieson, John; et al.
Abstract Bradyrhizobium sp. strain WSM1743 is an aerobic, motile, Gram-negative, non-spore-forming rod that can exist as a soil saprophyte or as a legume microsymbiont of anIndigofera sp. WSM1743 was isolated from a nodule recovered from the roots of anIndigofera sp. growing 20 km north of Carnarvon in Australia. It is slow growing, tolerates up to 1 % NaCl and is capable of growth at 37 °C. Here we describe the features ofBradyrhizobium sp. strain WSM1743, together with genome sequence information and its annotation. The 8, 341, 956 bp high-quality permanent draft genome is arranged into 163 scaffolds and 167 contigs, contains 7908 protein-coding genes and 75 RNA-only encoding genes and was sequenced as part of the Root Nodule Bacteria chapter of the Genomic Encyclopedia of Bacteria andArchaea project.